2014
DOI: 10.2478/s13531-013-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

On MHD unsteady reactive Couette flow with heat transfer and variable properties

Abstract: This study is devoted to investigate the effect of magnetic field on a reactive unsteady generalized Couette flow with temperature dependent viscosity and thermal conductivity. It is assumed that conducting incompressible fluid is subjected to an exothermic reaction under Arrhenius kinetics, neglecting the consumption of the material. The model nonlinear differential equations governing the transient momentum and energy balance are obtained and tackled numerically using a semi-discretization finite difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The velocity components (u1 ${u}_{1}$, w1 ${w}_{1}$) can be determined by slitting into real and imaginary parts of (22). The problem modeled by Makinde and Franks 64 is retrieved from our modeled problem by substituting K2=0 ${K}^{2}=0$ (i.e., rigid frame of reference).…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The velocity components (u1 ${u}_{1}$, w1 ${w}_{1}$) can be determined by slitting into real and imaginary parts of (22). The problem modeled by Makinde and Franks 64 is retrieved from our modeled problem by substituting K2=0 ${K}^{2}=0$ (i.e., rigid frame of reference).…”
Section: Problem Formulationmentioning
confidence: 99%
“…The thermal transport mechanism in a Couette flow of a chemically reactive power-law fluid inside a cylindrical annulus was reported by Makinde. 63 Makinde and Franks 64 inspected the impressive role of the activation energy on the unsteady Couette stream by considering variable fluid properties under a magnetic scenario. Das et al 65 reported the importance of Arrhenius kinetics in a time-sensitive gyrating Couette movement in a magnetic ambiance.…”
mentioning
confidence: 99%
“…Unsteady Couette flow through of a viscoelastic fluid through a parallel plate channel filled with a porous medium was studied by Attia et al [17] . Makinde and Franks [18] studied transient reactive MHD Couette flow with temperature dependent viscosity and thermal conductivity. Boundary conditions of all above researches were either constant or time-dependent velocity at the moving wall.…”
mentioning
confidence: 99%